2018
DOI: 10.1039/c8sm01281d
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional locomotion of liquid metal droplets driven by magnetic fields

Abstract: The locomotion of liquid metal droplets enables enormous potential for realizing various applications in microelectromechanical systems (MEMSs), biomimetics, and microfluidics. However, current techniques for actuating liquid metal droplets are either associated with intense electrochemical reactions or require modification of their physical properties by coating/mixing them with other materials. These methods either generate gas bubbles or compromise the stability and liquidity of the liquid metal. Here, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 49 publications
0
55
0
Order By: Relevance
“…The third one does not require the addition of magnetic materials; just pure LM droplets can be propelled by moving a permanent magnet. Shu et al reported an innovative method for controlling the locomotion of MLMTs using Lorentz force [100]. When a permanent magnet approaches the EGaIn droplet, the magnetic flux density B experienced by the droplet increases and induces a current j within the coils, which can be expressed as:…”
Section: Magnetic Propulsionmentioning
confidence: 99%
“…The third one does not require the addition of magnetic materials; just pure LM droplets can be propelled by moving a permanent magnet. Shu et al reported an innovative method for controlling the locomotion of MLMTs using Lorentz force [100]. When a permanent magnet approaches the EGaIn droplet, the magnetic flux density B experienced by the droplet increases and induces a current j within the coils, which can be expressed as:…”
Section: Magnetic Propulsionmentioning
confidence: 99%
“…Until now, electrification of liquid metal has been used almost exclusively to move fluids within otherwise static devices or within electrolytes. For example, CEW has been employed to make pumps (Tang et al, 2014a), mixers (Tang et al, 2014b), microactuators (Khoshmanesh et al, 2017;Li et al, 2020), and tunable antennas (Reichel et al, 2018;Wang et al, 2015), Liquid metals have also been moved using dynamic magnetic fields to induce a Lorentz force (Shu et al, 2018;Yu and Miyako, 2018), chemical reactions to induce unbalanced surface tension (Shu et al, 2020;Tang et al, 2013b;Zhang et al, 2015), electrostatic force (Zhang et al, 2019b), and ultrasound generated acoustic radiation force (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, interest in nontoxic gallium-based alloys, such as eutectic gallium-indium alloys EGaIn and Galinstan, has grown owing to their intriguing and unexpected properties, including high flexibility, low viscosity, and excellent fluidity. [1] Consequently, EGaIn and Galinstan have been used for various applications, such as pumps, [2,3] electrical devices, [4][5][6][7][8][9][10][11] actuators, [12][13][14][15][16] metamaterial devices, [17,18] wearable electronics, [19][20][21][22] and soft robotics. [23] Manipulating LMs as flexibly and freely as in the movie Terminator has long been a dream for many scientists across a range of scientific and technological disciplines, ranging from mechanics to biology.…”
Section: Introductionmentioning
confidence: 99%